Pengabdian Masyarakat Mahasiswa Di Pondok Pesantren Roudlhotul Ulum - Zhazha Zhazha; Mumun Mumun; Yusun Yusun; Banu Mahendro; Dedi Dedi; Yudha Yudha; Eko Sumartono; Yossie Yumiyati; Lina Widawati (Universitas Dehasen Bengkulu, 2023)
This PMM activity was carried out at the Roudlotul Ulum Islamic Boarding School, which is one of the Islamic boarding schools located in Jenggalu Village, Sukaraja Subdistrict, Seluma Regency, under the name Arraudhah Alhamid Foundation. The problem faced is that the location of the pesantren is quite far to seek treatment at the puskesmas or hospital. Erratic weather changes sometimes make students sick. Sometimes students also bring their own medicines from home, or teachers and teaching staff also prepare these medicines. In fact, there are many plants that can be used as herbal medicines to treat diseases. The method used was counseling and practice of making ginger candy and also handing over medicinal plant seeds. From the implementation of this activity, it provides benefits as a form of problem solving in the boarding school, through providing material about the benefits of family medicinal plants, practicing making ginger candy as a medicine to boarding school students, and also providing and planting medicinal plant seeds for the boarding school, especially for students.